ASSOCIATION OF LEPTOSPIRA INFECTION AND REPRODUCTIVE PROBLEMS IN A LARGE SHEEP FARM IN THE CENTRAL HIGHLANDS OF PERu - Flores M., Andrea (2009)
The association between leptospiral infection and reproductive problems in ewes from a large sheep enterprise in Junin, Peru, was evaluated in a Case-Control study during the breeding season of 2003. Serum samples from 2-10 year-old ewes with abortion or infertility problems (Case group, n = 220) and from ewes without reproductive problems (Control group, n = 220) were collected for the detection of antibodies against Leptospira serovar: pomona, hardjo, canicola, icterohaemorrhagiae, grippotyphosa, wolffi, ballum and bratislava by the microscopic agglutination test. The prevalence of Leptospira sp. was 24.8 ± 4.6%, corresponding 28.6 ± 7.0% to the Case group and 20.9 ± 5.9% to the Control group. No statistic association between leptospiral antibodies and reproductive problems was found by the Chi Square test. The highest serological prevalence (42.2%) was recorded for serovar ballum followed by icterohaemorrhagiae (31.2%). Animals with antibodies to more than one serovar of Leptospira were detected.